Metal Promoted Cyclocarbonylation Reactions in the Synthesis of Heterocycles - Aronica, Laura Antonella (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is focused on metal-catalyzed cyclocarbonylation reactions applied to the synthesis of heterocyclic rings of different sizes, including diastereoselective and enantioselective approaches, homogeneous and heterogeneous metal catalysis, and the application of these reactions to the total synthesis of natural products.